2015
DOI: 10.1149/2.0621507jes
|View full text |Cite
|
Sign up to set email alerts
|

The pH Dependence of Magnesium Dissolution and Hydrogen Evolution during Anodic Polarization

Abstract: The dissolution of magnesium (Mg) has been investigated with an electrochemical flow cell coupled to downstream analysis. The setup allows for polarization experiments and simultaneous determination of the amount of dissolved magnesium ions via inductively coupled plasma -mass spectroscopy (ICP-MS). Additionally, Mg dissolution was compared to hydrogen evolution measurements in the flow cell and also in standard beakers. Experiments were performed in unbuffered NaCl and in buffered solutions of various pH to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(61 citation statements)
references
References 33 publications
1
58
2
Order By: Relevance
“…[15][16][17] It has been reported that enrichment of surface impurities alone cannot account for the observed NDE since substantial enhanced catalytic activity was observed even for ultra-high purity Mg. 26 Recently, Mg surface films have been shown to sustain HER and may also contribute to increased rates of self-corrosion. 18,21,28,31,36 Studies also suggest that the impurities trapped in the film may provide cathodic sites to sustain HER. 16,27,37 We note that these mechanisms may have played a role in the high rates of self-corrosion observed, and that acceleration was likely facilitated at the high dissolution rates observed in our experiments.…”
Section: Resultsmentioning
confidence: 99%
“…[15][16][17] It has been reported that enrichment of surface impurities alone cannot account for the observed NDE since substantial enhanced catalytic activity was observed even for ultra-high purity Mg. 26 Recently, Mg surface films have been shown to sustain HER and may also contribute to increased rates of self-corrosion. 18,21,28,31,36 Studies also suggest that the impurities trapped in the film may provide cathodic sites to sustain HER. 16,27,37 We note that these mechanisms may have played a role in the high rates of self-corrosion observed, and that acceleration was likely facilitated at the high dissolution rates observed in our experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, the water reduction reaction can be enhanced on some cathodic sites produced by active dissolution of Mg in the anodic zone due to the well-known anodic HE. 35 As a result, pH can increase to some extent in the anodic sites which enlarge the surface area with high pH on MgZn 2 . At pH 4, it is found that the lowest pH (pH = 5.5) on MgZn 2 is higher than the bulk solution pH, which is probably due to the anodic HE and the migration of OH − from the higher pH zone (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…3,4,12,16,[21][22][23][24][25][26][27] On these metals, with relatively low electrochemical potential for oxidation, hydrogen evolution is always thermodynamically possible in the presence of water, but may be hindered by the presence of an oxide, hydroxide, or mixed film that physically separates the metal surface from the electrolyte. In some conditions, when the film is locally disrupted, such as for example during anodic polarisation in chloride-containing environment or at active corrosion sites (pits) during free corrosion, hydrogen evolution might occur locally, providing additional current sustaining corrosion propagation.…”
Section: Introductionmentioning
confidence: 99%